HEURISTIC ANALYSIS IN THE CONTEXT OF USER EXPERIENCE - Ortiz, Lais Caroline; Zuchi, Jederson Donizete (Revista Interface Tecnológica, 2022)
Faced with the growth in the number of people using interfaces, the rise of the User Experience area and the constant increase in specialist professionals in this area have become increasingly present, as companies need to think about how to deliver products with better experiences and interactions for meet the needs of users and, in this way, be better accepted in the market. With a qualitative paradigm and research with bibliographic and information survey on websites, articles and official documentation, this article aims and motivation to clarify the process and rules of heuristic analysis in the context of User Experience.
Keywords: UX; Usability; Heuristics; Nielsen